Serum cortisol concentrations during low dose dexamethasone suppression test to screen for Cushing's syndrome. Issue 6453 (3rd November 1984) - Kennedy, L; Atkinson, A B; Johnston, H; Sheridan, B; Hadden, D R
Abstract : Forty four subjects (23 obese controls, 11 patients with possible Cushing's syndrome, and 10 patients with definite Cushing's syndrome) underwent low dose (0 X 5 mg every six hours for two days) dexamethasone suppression tests during which serum cortisol concentration at 0800 and excretion of urinary free cortisol over 24 hours were measured. Serum cortisol concentration fell to below 60 nmol/1 (2 X 2 micrograms/100 ml) in 31 subjects and remained above 250 nmol/1 (9 X 1 micrograms/100 ml) in the 13 others. Excretion of urinary free cortisol showed a similar response, falling to below 110 nmol (40 micrograms)/24 h in 31 and remaining above 180 nmol (65 micrograms)/24 h in the 13 others. There was complete concordance between the two variables in terms of the pattern of response. Serum cortisol concentration fell to below 60 nmol/1 (2 X 2 micrograms/100 ml) in at least 97% (31 of a possible 32) of subjects without Cushing's syndrome. On the other hand, a serum cortisol concentration of above 250 nmol/1 (9 X 1 micrograms/100 ml) after low dose dexamethasone gave a false positive diagnosis of Cushing's syndrome in at most only one of 13 patients (7 X 7%). Measurement of serum cortisol concentration during the low dose dexamethasone test is simpler than, and as accurate and reliable as, measurements of urinary steroids.